A STUDY ONEMPLOYEE ENGAGEMENT PRACTICES OF KPO INDUSTRY (International Journal of Food and Nutritional Sciences, 2022)
The main aim of the study is to study the employee engagement practices in KPO industry and identifyemployee engagement practices in KPO industry among different demographic profile of employees. The study is conducted involving employee from KPO industry. The questionnaire was distributed to 385sample respondents. After receiving responses from sample respondents each form was checked for filter the completed forms and reconnect the respondents for to receive response to incomplete forms over the phone call for saving time. Forms furnishing irrelevant information and suffering inconsistency in information was rejected. After carefully studying the sampling techniques available, non-probability judgmental sampling technique was decided to be put to use for data collection for the present study.The data required for the study was collected from both the primary and secondary sources. Primary data was collected to get first hand information about a topic and for the purpose of analyzing information.This study is an attempt to help KPO industry ensure that the specific parameters/category of employee that the KPO industry wishes to focus on at any point of time and the Employee Engagement strategies that it is investing in are in sync or not.